Establecimiento de la calidad y composición química de los aceites esenciales de Aguacate ( Persea americana), Menta (Menthax piperita) y Eucalipto (Eucaliptus globulus) para su posible uso como fungicidas - Varas Diaz, Johan Alfredo (2024)
Plant extracts are a form of pest and disease control, which falls within the circle of sustainable agriculture, an interesting alternative because these extracts have secondary metabolites that give natural extracts anti-appetite and other characteristics (Barrera et al., 2018). The plant uses these compounds as part of its own defense mechanism; therefore, they can be used as bioproducts to improve quality and increase production since they act against plant pathogens. Essential oils are recognized as a valuable alternative for pest and fungal management in agriculture, due to their chemical composition, which exhibits antifungal properties against pests in economically important crops.